Integrative Systematics of Deep-Sea Invertebrates (International Journal of Animal Biodiversity, Conservation and Systematics ( IJABC), 2024)
Deep-sea invertebrates -- organisms inhabiting marine environments below 200 m, where high pressure, lowtemperature, perpetual darkness, and low food availability impose extreme physiological demands -- constitute a vastand largely uncharacterised component of global biodiversity, with conservative estimates suggesting that fewer than10% of deep-sea species have been formally described. The morphological convergence driven by the uniform deep-seaenvironment, combined with the rarity and fragility of specimens recovered by trawl or remotely operated vehicle (ROV)sampling, makes integrative systematic approaches combining morphology, multi-locus molecular barcoding, andtranscriptomics essential for reliable species delimitation and phylogenetic placement of deep-sea taxa. This studyapplied an integrative systematic framework to 284 deep-sea invertebrate specimens from seven phyla (Porifera,Cnidaria, Annelida, Mollusca, Arthropoda, Echinodermata, Hemichordata) collected by ROV (RV Polarstern; RV Meteor;RV Sarmiento de Gamboa) from 800-4,200 m depth across the Atlantic, Mediterranean, and Arctic deep-sea basins.Molecular barcoding (COI, 16S, 28S; n = 284 specimens) combined with morphological examination and micro-CTscanning identified 48 putative new species (confirmed by integrative diagnosis), of which 28 were formally described asnew to science. Multi-locus phylogenetic analysis (IQ-TREE2; RAxML-NG; ASTRAL-III) recovered nine new generic-levelplacements that alter established deep-sea invertebrate family classifications. Transcriptomic comparison of fivesympatric species pairs revealed convergent gene expression at pressure-response, cold-adaptation, andbioluminescence pathway genes (enrichment 6.4x above genome background; p < 0.001). These results demonstratethe power of ROV-enabled integrative systematics for accelerating deep-sea biodiversity inventory and provide amolecular reference library for environmental DNA (eDNA) monitoring of deep-sea invertebrate communities.